Pemanfaatan linguistik generatif transformasional dalam pengajaran pengembangan kalimat berbasis muatan lokal pada Siswa Sekolah Dasar - Dwipayana, I Kadek Adhi; Gotama, Putu Andyka Putra; Putrayasa, Ida Bagus (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research uses a library research approach that prioritizes philosophical analysis over empirical data testing. There are three important points studied in this research, namely learning sentence analysis in elementary school students using a transformative generative linguistic approach, the application of types of transformation in learning sentence analysis, and the relevance of learning sentence analysis by utilizing local content. The results of this study are projected to be used as a reference source for language teaching guidelines that further develop language creativity, especially the use of sentences. The generative transformational linguistic approach developed by Chomsky, offers an interesting theoretical framework for understanding sentence variation and its underlying structural transformations. Implementation of sentence analysis teaching based on a transformational generative linguistic approach to elementary school students requires implementation steps that are appropriate to the level of cognitive development and language skills of students at the elementary school level, namely the initial stage (first and second grade students), the middle stage (third grade students and four), and advanced stages (fifth and sixth grade students). Implementation of the transformational generative linguistic approach can be carried out through several stages, namely introducing the basic ideas of generative grammar, understanding the basic structure of sentences, understanding syntactic transformations, transformation exercises and case studies. Local cultural inclusion can be utilized in teaching sentences to elementary school students. Students can use language in their own cultural context, consider variations in linguistic expression, and explore the cultural strengths of sentence structure.